Competence managementas a factorof the organization adoptionto the external environmentin implementingthe personnel management strategy (Journal of Economic Research & Business Administration, 2016)
Company competencies representa rational combination ofknowledge and skillsof employeesthatit requiresa certain period oftime to achievethe objectives andexpected results. One of the trendsinhuman resource man-agementis to manage theprocess ofdeterminingthe application, evaluation, acquisition, promotion and development ofcompetenciesin the company. Consequently, HR-manager shoulddetermine whethercompetenciesin candidates forvacanciesin the primaryinterviewfor employment, as well as to analyze andpredict the possibilityof acquisitionand further development ofstaffto meet the needsof the company.The purpose ofthe definition, use, purchase, promotion, development and evaluationof personnel competen-ceof the company -the achievement of plannedresultsin the shortestpos-sible timeandto obtainthe greatest possiblebenefitto the company.
Keywords: competence; management competence; strategy; compe-tency model; the adaptation of the organization; the external environment; HR strategy